Are the treasures of game theory ambiguous? - Eichberger, Jürgen; Kelsey, David (Discussion paper series, 2008)
Goeree & Holt (2001) observe that, for some parameter values, Nash equilibrium provides good predictions for actual behaviour in experiments. For other payoff parameters, however, actual behaviour deviates consistently from that predicted by Nash equilibria. They attribute the robust deviations from Nash equilibrium to actual players’ considering not only marginal gains and losses but also total pay-offs. In this paper, we show that optimistic and pessimistic attitudes towards strategic ambiguity may induce such behaviour.
Keywords: Arbeitspapier; Graue Literatur